Data from: Climate change and the northern elephant seal (Mirounga angustirostris) population in Baja California, Mexico - García-Aguilar, María C.; Turrent, Cuauhtémoc; Elorriaga-Verplancken, Fernando R.; Arias-Del-Razo, Alejandro; Schramm, Yolanda (Data Archiving and Networked Services (DANS), 2019)
The Earth′s climate is warming, especially in the mid- and high latitudes of the Northern Hemisphere. The northern elephant seal (Mirounga angustirostris) breeds and haul-outs on islands and the mainland of Baja California, Mexico, and California, U.S.A. At the beginning of the 21st century, numbers of elephant seals in California are increasing, but the status of Baja California populations is unknown, and some data suggest they may be decreasing. We hypothesize that the elephant seal population of Baja California is experiencing a decline because the animals are not migrating as far south due to warming sea and air temperatures. Here we assessed population trends of the Baja California population, and climate change in the region. The numbers of northern elephant seals in Baja California colonies have been decreasing since the 1990s, and both the surface waters off Baja California and the local air temperatures have warmed during the last three decades. We propose that declining population sizes may be attributable to decreased migration towards the southern portions of the range in response to the observed temperature increases. Further research is needed to confirm our hypothesis; however, if true, it would imply that elephant seal colonies of Baja California and California are not demographically isolated which would pose challenges to environmental and management policies between Mexico and the United States. females estimateestimation of the total number of females from a single count using the expected proportion of females on land obtained with the RMM modelHeat waves ICheat waves on Cedros Island, 1957-1995maximum air temperature (month)monthly average maximum air temperature on Cedros Island, 1957-1995mean air temperature (month)monthly average mean air temperature on Cedros Island, 1957-1995minimum air temperature (month)monthly average minimum air temperature on Cedros Island, 1957-1995